Rozwój metodologii badań panelowych - Kowalski, Paweł (Panel Research Methodology Development, 2006)
The main goal of the article is an attempt to describe and systematize different panel research methodologies applied by research companies in a process of realization of consumer and retail panels. The author tries at the same time to provide a range of data delivered by individual panels as well as to consider the basic information on different panels carried out in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 535-544